The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0885412217693569
|View full text |Cite
|
Sign up to set email alerts
|

State Mandates, Housing Elements, and Low-income Housing Production

Abstract: In order to create low-income housing opportunities and mitigate exclusionary zoning, in 1968 Congress mandated that municipalities receiving comprehensive planning funds must create a housing element. In tandem, many states mandated that municipal housing elements must accommodate low-income housing needs. After examining empirical research for California, Florida, Illinois, and Minnesota, this review found aspirational success because those states rewarded the municipal planning process. In order to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…When it adopted the Housing and Development Act of 1968, Congress took a regional approach to connecting suburban housing opportunities with the housing needs of the central cities' poor and minority households. Congress mandated that cities receiving section 701 funds for general plans must include a housing element that focuses on local and regional housing needs [21]. A housing element, which is a chapter in a city's general plan, describes a city's housing goals, programs, and objectives.…”
Section: The Origins Of Allocating Housing Needsmentioning
confidence: 99%
“…When it adopted the Housing and Development Act of 1968, Congress took a regional approach to connecting suburban housing opportunities with the housing needs of the central cities' poor and minority households. Congress mandated that cities receiving section 701 funds for general plans must include a housing element that focuses on local and regional housing needs [21]. A housing element, which is a chapter in a city's general plan, describes a city's housing goals, programs, and objectives.…”
Section: The Origins Of Allocating Housing Needsmentioning
confidence: 99%
“…In the immediate years after 1926, many states adopted SZEA and many cities subsequently implemented zoning ([27], Figure 1). However, Euclidean zoning begat an enduring tension between states and cities regarding autonomy and development [27][28][29][30][31]. Under home rule, can city residents and elected officials pursue a neighborhood idyll that excludes low-income households?…”
Section: The Role Of Zoningmentioning
confidence: 99%
“…The authors then examined the zoning from 87 suburban cities in Los Angeles County to survey ADU zoning restrictions and reported that 61 suburbs (or 70%) required on-site parking, 42 (or 48%) stipulated a minimum lot-size, and 27 (or 31%) required covered parking [4]. In order to overcome ADU zoning restrictions nationally, the AARP and the American Planning Association (APA) created model ADU ordinances (partly based on California's ADU mandate) to influence planners in the same manner that the 1920s SZEA models influenced states [27,75]. The models provided three levels of development standards for fine-tuning a city's zoning: optimal (has the fewest restrictions), favorable (has modest restrictions), or minimal (may hinder production; [75]).…”
Section: Adus As Innovative Housingmentioning
confidence: 99%
“…Early 20th century housing plans were calls to reform slum conditions [55]. During the 1950s and 1960s, HUD's Section 701 funds supported comprehensive and housing plans that employed technical analyses to quantify needs and demand [31,33]. In the late 1970s, HUD allowed planners to implement regional allocation systems after recognizing that uncoordinated municipal responses could not reduce housing inequity [56].…”
Section: California's Housing Element Lawmentioning
confidence: 99%
“…After WW II, Congress passed the Housing Act of 1949 to advance slum clearance with urban renewal; however, a city could not receive slum clearance funds unless its urban renewal plan conformed to its general plan [31,32], Title I, Section 105. Soon after, federal officials found that small localities (25,000 persons or less) lacked housing and building codes that would guide federal investments [33] (p. 179).…”
Section: Introductionmentioning
confidence: 99%